2010
DOI: 10.1016/j.otsr.2010.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Distal leg fractures: How critical is the fibular fracture and its fixation?

Abstract: Level IV (prospective cohort study).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 26 publications
0
16
0
1
Order By: Relevance
“…Though metaphyseal tibial fractures rarely occur with fibular fractures [3], fibular fractures with distal, diaphyseal tibia fractures, that are mainly located in the supratubercular or media diaphyseal regions have an incidence of > 75% [4]. Surgical treatment of distal tibiofibular fractures with intramedullary nailing (IMN) is the preferred method of repair [5], even in very distal fractures [6].…”
Section: Introductionmentioning
confidence: 99%
“…Though metaphyseal tibial fractures rarely occur with fibular fractures [3], fibular fractures with distal, diaphyseal tibia fractures, that are mainly located in the supratubercular or media diaphyseal regions have an incidence of > 75% [4]. Surgical treatment of distal tibiofibular fractures with intramedullary nailing (IMN) is the preferred method of repair [5], even in very distal fractures [6].…”
Section: Introductionmentioning
confidence: 99%
“…6). Un autre facteur augmentant la stabilité de la fracture est l'ostéosynthèse de la fibula, comme l'ont rappelé récemment Bonneviale et al [9]. Elle doit être proposée facilement voire systématiquement dans notre expérience : au minimum par une broche d'alignement, voire une ostéosynthèse par plaque vissée.…”
Section: Fixation Externeunclassified
“…As for those comminuted cases usually associated with high energy trauma, soft tissue status sometimes should be considered much more over the union rate. [4,5] have reported that fibular fixation is a must for comminuted tibia fracture patterns.…”
Section: To Perform a Well-matched Pair Comparison In Clinicalmentioning
confidence: 99%
“…In the research of Bonnevialle et al [5], 126 cases of distal tibial fractures associated with fibular fractures were enrolled. The fibula lesions were not treated in 79 cases and the other 47 cases were fixed.…”
Section: To Perform a Well-matched Pair Comparison In Clinicalmentioning
confidence: 99%